The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.21203/rs.3.rs-1808216/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysimilarities In The Gut Metabolome Of Rabbits With Genetic Differences In Their Resilient Potential

Abstract: Background The gut-derived metabolites are key actors in the host-microbiota crosstalk and can have either beneficial or detrimental effects on the host. Gut metabolome could be a potential strategy to enrich the knowledge of host-gut interactions, providing another way of improving key traits such as animal resilience and welfare in livestock systems. Animal resilience has now become a critical livestock trait because of the high demand for more sustainable productions. Environmental variance (VE), the withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, research has delved into the molecular mechanisms underlying the impact of chronic stress on immune function, revealing the role of signaling pathways and cellular processes in mediating stress-induced immune dysregulation (Li et al, 2011). Additionally, the programming of vascular dysfunction by maternal stress has been linked to immune system implications, emphasizing the broader implications of stress on immune health (Casto-Rebollo et al, 2022).…”
Section: The Role Of Resilience In Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, research has delved into the molecular mechanisms underlying the impact of chronic stress on immune function, revealing the role of signaling pathways and cellular processes in mediating stress-induced immune dysregulation (Li et al, 2011). Additionally, the programming of vascular dysfunction by maternal stress has been linked to immune system implications, emphasizing the broader implications of stress on immune health (Casto-Rebollo et al, 2022).…”
Section: The Role Of Resilience In Immune Responsesmentioning
confidence: 99%
“…The study of resilience in the face of stress and adversity has also extended to non-human organisms, such as pigs and rabbits, where genetic and environmental factors influencing resilience have been investigated (Bai et al, 2020;Casto-Rebollo et al, 2021;Casto-Rebollo et al, 2022;Casto-Rebollo et al, 2020;Costa et al, 2022). These studies have revealed the essential role of the immune system, nervous system, and cell receptors in modulating resilience and responses to environmental perturbations.…”
Section: Introductionmentioning
confidence: 99%